2006
DOI: 10.2174/138945006775515491
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Dopamine Transmission by 5HT2C and 5HT3 Receptors: A Role in the Antidepressant Response

Abstract: Dopaminergic mesolimbic and mesocortical systems are fundamental in hedonia and motivation. Therefore their regulation should be central in understanding depression treatment. This review highlights the dopaminergic activity in relation to depressive behavior and suggests two putative receptors as potential targets for research and development of future antidepressants. In this article we review data that describe the role of serotonin in regulating dopamine release, via 5HT2C and 5HT3 receptors. This action o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
52
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 0 publications
1
52
0
Order By: Relevance
“…In a previous study (23), a polymorphism in the regulatory region of HTR3A shown to increase gene expression (24) was found to affect the improvement observed in depressed patients upon paroxetine treatment. In addition, other studies have suggested a link between 5-HT 3 receptor activation and the treatment/ etiology of depression (5,(25)(26)(27). Our data in combination with the association study by Yamada et al (20) suggest that the role of the 5-HT 3AB receptor in the etiology and treatment of depression may be interesting to investigate in greater detail.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In a previous study (23), a polymorphism in the regulatory region of HTR3A shown to increase gene expression (24) was found to affect the improvement observed in depressed patients upon paroxetine treatment. In addition, other studies have suggested a link between 5-HT 3 receptor activation and the treatment/ etiology of depression (5,(25)(26)(27). Our data in combination with the association study by Yamada et al (20) suggest that the role of the 5-HT 3AB receptor in the etiology and treatment of depression may be interesting to investigate in greater detail.…”
Section: Discussionsupporting
confidence: 79%
“…Presynaptic 5-HT 3 receptors are known to modulate the synaptic release of various neurotransmitters (3)(4)(5), whereas postsynaptic 5-HT 3 receptors are responsible for the fast excitatory response to serotonin (6). The role of the 5-HT 3 receptor in general physiology and pathophysiology is not well established.…”
mentioning
confidence: 99%
“…Moreover, our results suggest that an imbalance in the mesolimbic GABA-ergic system together with the alterations in DHEA levels may lead to the pathological behavioral outcomes observed in the FSL rats. The GABA-ergic system is an important regulator of dopaminergic neurons (Akiyama et al, 2004), which are relevant to depression (Dremencov et al, 2006;Friedman et al, 2007). Specifically, GABA A Rs within the VTA regulate dopamine output to the NAc (Bankson and Yamamoto, 2004;Yan et al, 2004), suggesting a modulatory role for these receptors in depression (Garcia-Alloza et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Conceivably, increasing 5-HT after CART peptides would activate 5-HT receptors. To date, at least fourteen subtypes of 5-HT receptors have been identified, including 5-HT 1B , 5-HT 2A , 5-HT 2C and 5-HT 3 receptors in the NAcc (Bruinvels et al 1993;Dremencov et al 2006;Ma et al 2006). Neurologically, NAcc, which belongs to dopaminergic mesolimbic and mesocortical systems, is associated with hedonic and motivational actions such as drug rewarding and reinforcement.…”
mentioning
confidence: 99%
“…However, the NAcc is emerged to play a role in depressive behavior because of the intimated interaction between dopaminergic systems and 5-HT receptors found in this region (Elhwuegi 2004). Activation of 5-HT receptors may lead to an increase in dopamine (Boulenguez et al 1998;Yan and Yan 2001) and possibly potentiate a therapeutic effect of antidepressants (Dremencov et al 2006). It is very possible that the effect can be enhanced after activation of serotonergic neurons in the DRN.…”
mentioning
confidence: 99%